The Effect of Providing Contraceptive Education on the Knowledge Level of Reproductive Age Couples in the Working Area of Pariaman Public Health Center - Prasetyaningsih; Setia Nisa (International Journal of Public Health Excellence (IJPHE), 2022)
The family planning program is an effort to improve the awareness and participation of the society through the maturity of marriage, birth control, family nurturing, and improvement of family welfare to create a happy and prosperous family. It can reduce 25% of maternal mortality and 18% infant mortality. The higher number of family planning means the more contraceptive use in reproductive age couples, then the higher the reduction number of maternal and infant mortality rates. This study aims to observe The Effect Of Providing Contraceptive Education On The Knowledge Level Of Reproductive Age Couples.This is a pre-experimental study with One Group Pretest-Posttest Design. The analysis used is paired sample t-test and Shapiro-Wilk test.. The research sampel was 50 of reproductive women spouses. It was obtained that the average of knowledge before contraceptive education was given is 44.56 with 15.38 of standard deviation. However, the average of knowledge after contraceptive education was given was given is 61,26 with 12,14 of standard deviation. It shows that the difference of the mean value before and after giving contraceptive education is 16.70 with 10.00 of standard deviation. Statistical test results obtained value of P-value = 0.000. There is a significant effect of giving contraceptive education to the knowledge level of couples with reproductive age in Pariaman Public Health Center in 2020 .The public health center is expected to improve family planning services for couples in fertility age by providing continuous counseling to increase their understanding of choosing and using proper contraception consistently.